EDUCATION FOR COMMUNITY IN EFFORTS TO PREVENT DRUG USED IN SEI PANGERAN KECAMATAN ILIR TIMUR I PALEMBANG - Ridwan, Ridwan; Shobur, Sherli; Sulaiman, Sulaiman (Martabe : Jurnal Pengabdian Kepada Masyarakat, 2021)
Background, Drugs can damage human health both physically, emotionally and the behavior of the user. an increase in drug trafficking during 2019 from the previous year of 0.03 percent. Most users are aged 15 to 65 years and exceed the three million people. more than 4 million Indonesians are drug users. The prevalence of abuse among students and college students is 3.21 percent or the equivalent of 2 million students who have abused drugs in 2018. Meanwhile, drug use among workers is 2.1 percent or more than 1.5 million people. So drugs are not only in Indonesia yes, around the world it's about the same. But in Indonesia we have increased by 0.03 percent. Approximately 3,600,000 people use this in Indonesia, "the trend of recruiting drug dealers in Palembang, South Sumatra is not only targeting housewives but also students on Palembang campuses. Purpose, This educational activity on the prevention of drug use aims to increase public knowledge of drug abuse methods, using extension methods and distributing leaflets, before counseling was carried out the first measurement, then monitoring was carried out two weeks later on the target group of 66 participants. The results, there was an increase in the knowledge of the target group from before and after the counseling was carried out. , the extension method is one of the effective media to educate the public on the prevention of drug use.